Evaluation of disease resistance and tolerance to elevated temperature stress of the selected tissue-cultured Kappaphycus alvarezii Doty 1985 under optimized laboratory conditions - Azizi, Azhani; Mohd Hanafi, Nursyuhaida; Basiran, Mohd Nazir; Teo, Chee How (Springer Verlag (Germany), 2018)
Information on the abiotic stress tolerance and ice–ice disease resistance properties of tissue-cultured Kappaphycus alvarezii is scarce and can pose a big hurdle to a wider use of tissue-cultured seaweed in the industry. Here, we reported on a study of seaweed-associated bacteria diversity in farmed and tissue-cultured K. alvarezii, and ice–ice disease resistance and elevated growth temperature tolerance of tissue-cultured K. alvarezii in laboratory conditions. A total of 40 endophytic seaweed-associated bacteria strains were isolated from 4 types of K. alvarezii samples based on their colony morphologies, Gram staining properties and 16S rRNA gene sequences. Bacteria strains isolated were found to belong to Alteromonas sp., Aestuariibacter sp., Idiomarina sp., Jejuia sp., Halomonas sp., Primorskyibacter sp., Pseudoalteromonas sp., Ruegeria sp., Terasakiella sp., Thalassospira sp. and Vibrio sp. Vibrio alginolyticus strain ABI-TU15 isolated in this study showed agar-degrading property when analyzed using agar depression assay. Disease resistance assay was performed by infecting healthy K. alvarezii with 105 cells/mL Vibrio sp. ABI-TU15. Severe ice–ice disease symptoms were detected in farmed seaweeds compared to the tissue-cultured K. alvarezii. Besides disease resistance, tissue-cultured K. alvarezii showed better tolerance to the elevated growth temperatures of 30 and 35 °C. In conclusion, our overall data suggests that tissue-cultured K. alvarezii exhibited better growth performance than farmed seaweeds when exposed to elevated growth temperature and ice–ice disease-causing agent.